2019
DOI: 10.1016/j.eurox.2019.100025
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy related cancer in Apulia. A population based linkage study

Abstract: Objective Despite a quite large number of papers in literature, the current incidence of pregnancy associated cancer still remains uncertain. Moreover, different inclusion criteria and time intervals considered after delivery make these data poorly comparable. The aim of this study was to investigate the incidence of PACs in Apulia, an Italian region, while stressing differences or similarities with other populations. Study design We collected 682,173 pregnancies from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The selected papers were published from 1995 to 2019, most of them after 2010. Of these, 13 were conducted in the USA [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 ], 7 in Europe [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ], mainly in the northern Europe, and 4 in Australia [ 2 , 3 , 25 , 26 ]. The majority of the studies were based on national registries.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The selected papers were published from 1995 to 2019, most of them after 2010. Of these, 13 were conducted in the USA [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 ], 7 in Europe [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ], mainly in the northern Europe, and 4 in Australia [ 2 , 3 , 25 , 26 ]. The majority of the studies were based on national registries.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies investigated the evolution of the incidence of PAC overall over calendar years. Three studies did not find a clear trend [4,23,24], while three studies found an increase in the incidence [2,14,20]. Two of them also investigated the relationship of the trend with a possible increase in age of mothers [2,20] and found that the trend was present even after adjusting for maternal age.…”
Section: Definition and Estimated Frequency Of Pacmentioning
confidence: 98%
See 3 more Smart Citations